Measure of Union in Terms of Measure of Intersection

From the definition of a measure, we require μ(A)+μ(B)=μ(AB) whenever AB=. The following result handles cases in which AB, that is, they overlap, by introducing an additional term.

Theorem

Given a measure μ on the σ-algebra F, for A,BF:

μ(A)+μ(B)=μ(AB)+μ(AB).

The primary utility of this result is to prove the measure theory inclusion exclusion principal, with the base case there being a more intuitively obvious version of the above

μ(AB)=μ(A)+μ(B)μ(AB)

and resembling the standard inclusion exclusion principle, where measuring the union of the two sets is equivalent to measuring them separately, and then accounting for double counting the overlap:

Proof

Consider that:

AB=A(BA)andAB=B(AB)

and hence:

μ(AB)=μ(A)+μ(BA)andμ(AB)=μ(B)+μ(AB)

given that A and BA are disjoint by definition of the set difference, and likewise for B and AB.

Now, given the sum of the above expressions in terms of μ(A) and μ(B) respectively, we have:

μ(A)+μ(B)=μ(AB)μ(BA)+μ(AB)μ(AB)=2μ(AB)(μ(BA)+μ(AB)+μ(AB))+μ(AB)=2μ(AB)μ((BA)(AB)(AB)+μ(AB)=2μ(AB)μ(AB)+μ(AB)=μ(AB)+μ(AB)